2022
DOI: 10.3390/su14127061
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Safeties and Mobilities on the Land in Arctic North America: A Systematic Approach to Identifying the Root Causes of Disaster

Abstract: Amid the surge in research on mobility and migration in the context of environmental change, little research has focused on the experiences of people for whom travel is cyclical and a part of daily, weekly, or seasonal life. For Inuit in Arctic North America, the land is the heart of cultural and community life. Disruption to time spent on the land is reported to impact the emotional health and well-being of individuals and communities. There is concern that environmental change is creating barriers to safe tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 183 publications
0
12
0
Order By: Relevance
“…Land and place are central to Indigenous Peoples’ lives and livelihoods, and thus the health and wellbeing impacts being experienced from climate and environmental change. For Indigenous Peoples, as Davis et al (2022) highlight, "the land is the heart of cultural and community life" [ 38 :2]. Just as the reviewed literature points to the centrality of land and place to Indigenous Peoples, so too does it indicate that "impacts , adaptation , and vulnerability are highly place- and culture-specific" [ 55 :1263] and that the "health of people and place demand an integrated engagement" [ 56 :5772].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Land and place are central to Indigenous Peoples’ lives and livelihoods, and thus the health and wellbeing impacts being experienced from climate and environmental change. For Indigenous Peoples, as Davis et al (2022) highlight, "the land is the heart of cultural and community life" [ 38 :2]. Just as the reviewed literature points to the centrality of land and place to Indigenous Peoples, so too does it indicate that "impacts , adaptation , and vulnerability are highly place- and culture-specific" [ 55 :1263] and that the "health of people and place demand an integrated engagement" [ 56 :5772].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 17 articles (44.7%) identified that ecosystem changes globally are creating threats to human safety. Most notably, natural calamities or environmental hazards such as flooding were known to increase accidental injury or death [ 32 , 35 , 38 , 48 , 50 , 58 ]. Subsequent erosion, particularly in coastal regions of Latin America and the Circumpolar North, was also tied to these health risks by causing infrastructure instability [ 42 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations